Monitoring the impact of EU F-gas regulation on HFC-134a emissions through a comparison of top-down and bottom-up estimates - Saurabh Annadate; Enrico Mancinelli; Barbara Gonella; Federica Moricci; Simon O’Doherty; Kieran Stanley; Dickon Young; Martin K. Vollmer; Rita Cesari; Serena Falasca; Umberto Giostra; Michela Maione; et al. (Environmental Sciences Europe)
Abstract HFC-134a is the most prevalent hydrofluorocarbon used as a replacement for ozone-depleting CFCs and HCFCs. Due to its high global warming potential, it is regulated under various European and global frameworks, underscoring the importance of tracking its emissions. Emissions derived by the commonly used, bottom-up, methodology are affected by a certain degree of uncertainty. The bottom-up estimates can be aided with an independent top-down estimate based on atmospheric observations combined with an atmospheric transport model. This study presents HFC-134a emissions for Europe, with a specific focus on Italy, from 2008 to 2023. The emissions were estimated using a Bayesian inversion methodology, based on atmospheric observations collected at four European stations. Our analysis reveals a slightly increasing trend in HFC-134a emissions for Italy from 2008 to 2015 of 0.17 $${\mathrm{Gg\,yr}^{-1}}$$ Gg yr - 1 , followed by a steady decrease thereafter, highlighting the effect of European regulation on fluorinated gases that came into force in 2014. We observed a reduction in HFC-134a emissions in the Po Basin inferred from the inversion method for 2020, likely due to mobility restrictions imposed during the COVID-19 pandemic. The observed mild seasonality in emissions may be partly attributed to higher air-conditioning activity during summer. Comparison with the Italian National Emission Inventory indicates an improvement in iterative bottom-up estimates, with the 2024 inventory emission trend post-2015 aligning closely with our inversion results. This study emphasises the need for collaboration between the two independent approaches to enhance the accuracy of emission estimates. Such cooperation is crucial to narrowing the gap in quantifying emissions of potent greenhouse gases and effectively assessing the progress of international policies and regulations.